DINAMIKA MOTIVASI DAN KINERJA PETANI DALAM PENGELOLAAN USAHATANI HIDROPONIK DI KOTA KENDARI - Irsan Jait; Salahuddin Salahuddin; Yoenita Jayadisastra (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The development of urban agriculture through hydroponic farming systems has emerged as a promising alternative for enhancing food security and improving community welfare amid the increasing scarcity of agricultural land. The success of hydroponic farming management is determined not only by farmers' technical competence in cultivation practices but also by their motivation, which is reflected in their farm management performance. This study aimed to analyze the dynamics of farmers' motivation and describe their performance in managing hydroponic farming systems in Kendari City, Indonesia. A qualitative approach with a descriptive research design was employed. The study involved 17 hydroponic farmers selected purposively based on their experience and active engagement in hydroponic farming. Data were collected through in-depth interviews, field observations, and documentation, and were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings revealed that farmers' motivation develops dynamically through the interaction of intrinsic and extrinsic motivation. Intrinsic motivation was driven by livelihood needs, the desire to increase income, and commitment to business development, whereas extrinsic motivation was influenced by a supportive business environment, accessible markets, and the relatively short hydroponic production cycle. The interaction between these dimensions forms a motivational reinforcement cycle, which strengthens farmers' commitment to sustaining and expanding their farming enterprises. Furthermore, this dynamic motivation is translated into improved performance, as reflected in increased production output, the ability to maintain product quality, and timely farm management, collectively conceptualized as integrated farmer performance capability. The findings suggest that the success of hydroponic farming depends not only on technical cultivation practices but also on strengthening farmers' motivation and their adaptive capacity to respond to changes in the agribusiness environment.